THE IMPACT OF THE CSR ( CORPORATE SOCIAL RESPONSIBILITY ) PROGRAM ON THE WELFARE OF THE COMMUNITY AROUND PTPN IV KEBUN ADOLINA - Rikki Pratama; Aulia Juanda Djaingsastro (RADJA PUBLIKA, 2026)
This study aims to analyze the impact of PTPN IV Kebun Adolina's Corporate Social Responsibility (CSR) program on the welfare of the community surrounding the company's operational area. The study used a descriptive quantitative approach with locations in Pegajahan, Lubuk Pakam, and Perbaungan Districts, Serdang Bedagai Regency. The research sample consisted of 71 respondents determined using the Slovin formula with a purposive sampling technique. Data were collected through questionnaires, interviews, and documentation, then analyzed using multiple linear regression with the help of SPSS. The results of the study indicate that CSR Education has a positive but insignificant effect on community welfare. Meanwhile, CSR Health, CSR Economic, and CSR Social each have a positive and significant effect on community welfare. Simultaneously, all CSR variables have a significant effect on community welfare with a significance value of 0.000 < 0.05 and F count of 244.374. This indicates that the CSR program as a whole provides a strong contribution to improving the social welfare of the community around PTPN IV Kebun Adolina.